A class of reversible quadratic polynomial vector fields on S-2 - Pereira, Weber F. [UNESP]; Pessoa, Claudio (Academic Press Inc. Elsevier B.V., 2010)
We study a class of quadratic reversible polynomial vector fields on S-2. We classify all the centers of this class of vector fields and we characterize its global phase portrait. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Reversible polynomial vector fields; Centers; Limit cycles; Phase portrait